1998
DOI: 10.1159/000055476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pituitary Adenylate-Cyclase-Activating Polypeptide on the Direct-Current Electroretinogram of the Rabbit Eye

Abstract: Pituitary adenylate-cyclase-activating polypeptide (PACAP) is a recently discovered neuropeptide present in two different forms, PACAP-27 and PACAP-38. Both peptides stimulate the catalytic enzyme adenylate cyclase in pituitary cells. This enzyme is important also regarding the function of the retinal pigment epithelium (RPE). The purpose of the study was to investigate possible influences of PACAP on the rabbit retina and the RPE as reflected in the direct-current (d.c.) electroretinogram (ERG) and the standi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Other studies indicate that endogenous PACAP is important in maintaining the antiapoptotic mechanisms 35,36 . Functioning PACAP receptors in both the neural retina and pigment epithelial cells have been confirmed by electroretinogram examinations, showing that intraocularly infused PACAP27 and –38 induced changes in the electrical waves reflecting the activity of both the pigment layer and the neural retina 37 …”
Section: Effects Of Pacap In the Retinamentioning
confidence: 86%
See 1 more Smart Citation
“…Other studies indicate that endogenous PACAP is important in maintaining the antiapoptotic mechanisms 35,36 . Functioning PACAP receptors in both the neural retina and pigment epithelial cells have been confirmed by electroretinogram examinations, showing that intraocularly infused PACAP27 and –38 induced changes in the electrical waves reflecting the activity of both the pigment layer and the neural retina 37 …”
Section: Effects Of Pacap In the Retinamentioning
confidence: 86%
“…35,36 Functioning PACAP receptors in both the neural retina and pigment epithelial cells have been confirmed by electroretinogram examinations, showing that intraocularly infused PACAP27 and -38 induced changes in the electrical waves reflecting the activity of both the pigment layer and the neural retina. 37 In retinal pigment epithelial cells, PACAP inhibits the interleukin-1(IL-1)-induced IL-6, -8, and monocyte chemotactic protein-1 expression. 27 Muller glial cells are one of the target cells for PACAP.…”
Section: Effects Of Pacap In the Retinamentioning
confidence: 99%
“…More importantly, this simple approach may be expanded to further increase the viability of the cells. We are in the process of studying the impact of anchoring other bioactive peptides with known neurotrophic effects such as VIP and PACAP (Jarkman et al, 1998;Kishi et al, 1996) in addition to the RGDS-CBP peptide. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have revealed that endogenous PACAP is important in maintaining anti-apoptotic mechanisms (Racz et al 2006(Racz et al , 2007. Functioning PACAP receptors in both the neural retina and pigment epithelial cells have been confirmed by electroretinography, with changes in the electrical wave reflecting the activity of both the pigment layer and the neural retina (Jarkman et al 1998). …”
Section: Pacap Receptors In the Eyementioning
confidence: 91%